Comprometimento da função pulmonar em indivíduos curados de tuberculose pulmonar: uma revisão de escopo - Batista, Lidiane Cardoso (Brasil, 2022)
The aim of the review was to map changes in lung function in individuals cured of PTB. Scope review that followed the JBI methodology. We considered studies performed in participants cured of PTB (≥18 years), of both sexes, that evaluated lung function regardless of the measurement method, which were performed in any clinical and geographic context, in any language. The searches were carried out in the information sources: CINAHL (EBSCOhost), EMBASE, Google Scholar, LILACS (BVS), MEDLINE (PubMed), PEDro, SPORTDiscus (EBSCOhost) and Web of Science – Core Collection, from the beginning of April 10 to May 27, 2022. The selection of studies was performed on the Rayyan platform, by two independent reviewers. Data were extracted using an extraction instrument developed by the reviewers themselves. Six studies were selected from the 2,224 possibly eligible records, with a combined sample of 4,440 participants and age range from 35 to 75 years. The percentage of individuals cured of PTB who had impaired lung function ranged from 19.3% to 62.7%, the most reported change in lung function was obstructive ventilatory disorder (4/6), the main determinants of impaired lung function were late treatment initiation, low education, smoking and history of HIV infection, and the method of measurement of pulmonary function reported in the studies was spirometry.